The Influence of Learning Media on Improving Underpassing in Terms of Student Learning Motivation - Dian Doni Krisyana; Dedi Supriadi; Vicky Ahmad Karisman (Universitas Negeri Semarang, 2026)
This study aimed to determine the effect of instructional media on forearm passing ability in volleyball and to examine whether learning motivation moderates this effect among Grade XII students at SMA Pasundan Banjaran. A quasi-experimental design with a Nonequivalent Control Group Design and pretest–posttest scheme was employed. The sample consisted of 35 students divided into an experimental group (n=17, Class XII-A) receiving instructional media treatment and a control group (n=18, Class XII-B) taught using conventional methods. Forearm passing ability was measured through pretest and posttest assessments, while learning motivation was assessed using a validated questionnaire. Data were analyzed using moderated regression analysis. Results showed that learning motivation significantly affected forearm passing ability (β=0.032, t=5.882, p<0.05), and the interaction between instructional media and motivation was also significant (β=0.014, t=30.464, p<0.05), indicating a moderation effect. Instructional media alone did not significantly affect passing ability (p=0.256). These findings suggest that the effectiveness of instructional media in improving forearm passing is contingent on students’ level of learning motivation, highlighting the importance of motivation-enhancing strategies in physical education.